Bahasa dan budaya: Menjadi pilar identitas nasional indonesia - Firdaus, Sheva Anella (Maliki Interdisciplinary Journal, 2025)
This study highlights the importance of preserving language and culture to strengthen unity and face the challenges of globalization. Bahasa Indonesia serves as asymbol of unity within diversity, while culture embodies local values that shape national character.In a multicultural country like Indonesia, language and culture hold a strategic position as the main pillars of national identity formation. Language and culture play vital roles in shaping Indonesia’s unifies the nation while cultural diversity reflects its rich identity. All things considered, language plays a multifaceted and intricate function in Indonesian culture identity formation. Language serves as the primary foundation for the richness and diversity of the countr’s culture, not only as a tool for communication. The Indonesian people can guarantee that their cultural identity will continue to be robust and and significant in the future by working together to protect and honor the many languages that are currently spoken.